Voices of the Buffer Zone: Harmonizing Language, History, and Biology in Instructional Media Development. - Gina Muta'affif; Dewinta Priti Wijayanti; Iva Novita; Erinda Salsa Billa; Ifa Muhimmatin (Assyfa Learning Journal, 2024)
Contextual instructional media integrating local history and biodiversity into accessible bilingual formats remain scarce in secondary education. To bridge this gap, this study developed and evaluated the feasibility of an interdisciplinary bilingual booklet (Indonesian–English) framing the local history, flora, fauna, and conservation messages of the Ijen buffer area in Banyuwangi as a contextual learning resource. Utilizing a Research and Development (R&D) model comprising analysis, development, validation, revision, and readability testing, the project involved student developers from English Language Education, Biology Education, and History Education programs. Data were collected via expert validation and user response questionnaires, subsequently analyzed through descriptive quantitative methods. Findings demonstrated high instructional feasibility across all expert evaluations: History (88.5%), Biology (90.2%), and English (86.7%), while student trial user responses yielded a highly positive rating of 87.6%. In conclusion, the resulting bilingual booklet offers a validated, multidisciplinary instructional medium that harmonizes local socio-ecological knowledge with disciplinary pedagogy, establishing a contextual learning resource tailored for Madrasah Aliyah education.